Determinants of Financial Distress in Construction State-Owned Enterprises Listed on the Indonesian Stock Exchange for the Period 2015-2024 Based on Altman Z-Score - Bambang Susilo; Asyari (Majapahit Journal of Islamic Finance and Management, 2026)
State-owned construction companies face structural financial pressures due to massive debt burdens to finance national infrastructure projects, exacerbated by the COVID-19 pandemic, which caused a 5.67% contraction in the construction sector in 2020, resulting in the suspension of trading of PT Waskita Karya and PT Wijaya Karya shares, which could potentially be delisted from the Indonesia Stock Exchange. This condition confirms that state-owned company status does not provide immunity from bankruptcy, as evidenced by PT Merpati Nusantara Airlines and PT Istaka Karya, which have been declared bankrupt. This study analyzes financial distress conditions based on the Altman Z-Score and identifies the influence of Operating Cash Flow, Company Size, Asset Growth, and Company Age on financial distress for the period 2015–2024, based on Agency Theory and Signaling Theory. Secondary data from four state-owned construction companies listed on the IDX were analyzed using multiple linear regression with SPSS version 31. PT Waskita Karya recorded the lowest Z-Score of −1.96, placing it in the distress zone. Partially: Operating Cash Flow had no significant effect (p = 0.457 > 0.05); Company Size had a significant negative effect (p < 0.001 < 0.05); Asset Growth had a significant positive effect (p = 0.030 < 0.05); Company Age had no significant effect (p = 0.494 > 0.05). Simultaneously, the four variables have a significant effect (p < 0.001 < 0.05) with an Adjusted R² of 47.7%, confirming that the financial distress of state-owned construction companies is multidimensional and requires holistic improvement interventions.